The Reported Adverse Events of Metformin: A Descriptive Analysis Using Data from VigiBase - Ahmad, Nehad Jaser (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: Metformin is a well-established component of diabetes management. It is generally safe and well-tolerated but may cause several adverse events. The present study aimed to describe the reported adverse events of metformin. Methods: This was a descriptive analysis that was conducted using data from VigiBase to describe the reported adverse events of metformin use. Results: Till October 23, 2022, 100,993 metformin adverse event reports were submitted to the world health organization’s global database (VigiBase). More than 57% of the patients were female and 42.49% of them were male. Conclusions: Gastrointestinal problems, abnormalities of metabolism and nutrition, general disorders, and conditions at the administration site were the most frequently reported side effects of metformin use. To reduce metformin adverse medication events, appropriate interventions such as targeted education should be implemented. Pharmacists should monitor their patients continuously to ensure the safe use of the medication.